The ecology and control of earthworms on golf courses - Bartlett, Mark D. (Cranfield University, 2006)
Earthworm casts on golf courses affect the playability of the turf and can potentially damage mowing equipment. Traditionally this problem has been limited using chemical controls. It is estimated that 0.6% of the total UK land surface is occupied by golf courses, therefore, the land management strategies which green keepers adopt with respect to the application of chemicals has a major environmental impact. The aim of this thesis was to investigate the ecology and potential control of earthworm casting in golf turf in environmentally sustainable ways. A quadrat survey of earthworm casts was conducted over two years at five golf courses in Bedfordshire and Buckinghamshire, UK. Using generalized linear models and forward multiple stepwise regression, an internally validated predictive model of earthworm casting activity was constructed. Annual activity on surfaces was predicted using five physicochemical parameters of which C: N and total inorganic nitrogen were the most important. Environmental parameters were also used to predict monthly earthworm activity, with evapotranspiration and rainfall representing the most significant variation. ' Mustard extraction surveys were used to investigate species diversity and community structure of earthworms. Four dominant species were identified (Aporrectodea rosea, Lunibricus rubellus, Aporrectodea longa and Lumbricus terrestris). It is likely that A. longa and L. terrestris, the two must abundant anecic forms, cause the greatest problems to green keepers as these are the largest of the four earthworm species. The microbial community of soil represents the earthworm's primary food source. An analysis of the microbial community size (using chloroform-extraction) and community structure (using phospholipid fatty acid [PLFA] analysis) showed that different surfaces found on golf courses supported significantly distinct and consistent microbial communities. Differences in population size and structure were evident at different depths through all golf course soil profiles investigated. Individual surface types were comparable, irrespective of geographical location. Therefore different surfaces and depths through the soil profile on golf courses represent different earthworm habitats. An investigation of the effects of different construction techniques and materials used in the golf industry on the rate of earthworm cast formation was made. This showed no effect of construction on the vertical distribution of earthworms, but the rate of casting increased on the sand dominated surfaces. It is proposed that this is due to the lower calorific value that this soil represents to the earthworms. This knowledge was applied in an earthworm cast mitigation experiment, reducing casting rates by stimulating the size of the microbial community with glucose solution. Control through physical exclusion of earthworms to the surface using a buried mesh was also trialled and significantly reduced earthworm casts, however no causal mechanism could be elucidated. This study has advanced the understanding of earthworm ecology on golf courses, deriving mechanistic understandings of this system as a whole. This will lead to a more environmentally sustainable approach to the control of earthworms on golf courses.